-2
$\begingroup$

I am working on a project to determine the Jones polynomial for the torus links and a class of links which I call tst links. Their braid words are respectively given by $$(\sigma_1 \sigma_2 \cdots \sigma_{p-1})^q \in B_p$$ and $$(\sigma_1^2 \sigma_2 \sigma_3 \cdots \sigma_p)^q \in B_{p+1}$$

I would like to know if anyone familiar with the Ocneanu approach, Chern-Simons Theory approach, and the Burau representations approach can evaluate the Jones polynomials and give a clear, detailed explanation.

$\endgroup$
1
4
$\begingroup$

Representation theory approach

First note that the trace of a braid $b$ from $B_p$ is given by the sum over all irreducible representations of the symmetric group $S_p$ given by the Young tableux $Y$ of $p$ nodes: $$\text{tr}(b) = \sum_Y \tilde W_Y(q,\lambda) \text{tr}(\pi_Y(b))$$ where $\tilde W_Y(q,\lambda)$ is the weight of the tableau $Y$ and $\pi_Y(b)$ is the representation of $b$ corresponding to the tableau $Y$.

Then it is given that $\text{tr}(\pi_Y(b)) = 0$ unless $Y$ is of the form with $(\beta+1)$ boxes in the first row, then $1$ box in each of the $\gamma$ rows that follow:

$Y_{\beta,\gamma}=$Young tableau

The weight of the tableau $Y = Y_{\beta, \gamma}$ is given by $$\tilde W_Y(q,\lambda) = \left(\dfrac{1-q}{1-\lambda q} \right)^p \dfrac{R_Y(q,\lambda)}{Q_Y(q)}$$ where $$R_Y(q,\lambda) = (1-\lambda q)(q-\lambda q)(q^2-\lambda q) \cdots (q^\beta -\lambda q) \times (1-\lambda q^2)(1-\lambda q^3)\cdots (1-\lambda q^{\gamma+1})$$

$$ = \prod_{i=0}^\beta (q^i-\lambda q)\times q^{1+2+\cdots+\gamma}(q^{-1}-\lambda q)(q^{-2}-\lambda q)\cdots(q^{-\gamma}-\lambda q) = q^{1+2+\cdots+\gamma}\prod_{i=-\gamma}^\beta (q^i-\lambda q) = q^{\frac{\gamma(\gamma+1)}{2}}\prod_{i=-\gamma}^\beta (q^i-\lambda q)$$

and $Q_Y$ is given by $$Q_Y(q) = (1-q)(1-q^2)\cdots (1-q^\beta) \times (1-q^\gamma)(1-q^{\gamma-1})\cdots (1-q) \times (1-q^{\gamma+\beta+1})$$ Using the notation $[n] = 1-q^n$, $[n]! = [n][n-1]!$ and $[0]!=1$, we can write it as $$Q_Y(q) = [\beta]![\gamma]!(1-q^p)$$ The remaining piece of information needed to calculate the trace is the trace $\text{tr}(\pi_Y(b))$ for the Young tableaux $Y = Y_{\beta,\gamma}$ specified above and $b=(\sigma_1\sigma_2\cdots\sigma_{p-1})^m$.

For coprime $m$ and $p$, this is given by $$\text{tr}(\pi_Y((\sigma_1\sigma_2\cdots\sigma_{p-1})^m)) = (-1)^\gamma q^{\beta m}$$

This is related to the fact that $(\sigma_1\sigma_2\cdots\sigma_{p-1})^q$ is in the center of the braid group $B_p$ but I don't know (1) why there is such connection, and (2) why this braid word is in the center.

Putting the pieces of information together, we have $$\text{tr}((\sigma_1\sigma_2\cdots\sigma_{p-1})^m) = \sum_{\begin{matrix} \beta+\gamma+1=p \\ \beta,\gamma \geq 0 \end{matrix}} (-1)^\gamma q^{\beta m} \left(\dfrac{1-q}{1-\lambda q} \right)^p \dfrac{q^{\frac{\gamma(\gamma+1)}{2}}}{[\beta]![\gamma]!(1-q^p)}\prod_{i=-\gamma}^\beta (q^i-\lambda q) $$

Hence the 2-variable Jones polynomial is given by $$X_{\text{Cl}((\sigma_1\sigma_2\cdots\sigma_{p-1})^m)}(q, \lambda) = \left(-\dfrac{1-\lambda q}{\sqrt \lambda (1-q)}\right)^{p-1} \sqrt \lambda^{(p-1)m} \times \sum_{\begin{matrix} \beta+\gamma+1=p \\ \beta,\gamma \geq 0 \end{matrix}}(-1)^\gamma q^{\beta m} \left(\dfrac{1-q}{1-\lambda q} \right)^p \dfrac{q^{\frac{\gamma(\gamma+1)}{2}}}{[\beta]![\gamma]!(1-q^p)}\prod_{i=-\gamma}^\beta (q^i-\lambda q)$$ $$= \left(\dfrac{1-q}{1-\lambda q} \right) \lambda^{\frac{(p-1)(m-1)}{2}} \sum_{\begin{matrix} \beta+\gamma+1=p \\ \beta,\gamma \geq 0 \end{matrix}} (-1)^{p-1-\gamma} q^{\beta m} \dfrac{q^{\frac{\gamma(\gamma+1)}{2}}}{[\beta]![\gamma]!(1-q^p)}\prod_{i=-\gamma}^\beta (q^i-\lambda q) $$ $$= \left(\dfrac{1-q}{1-\lambda q} \right) \lambda^{\frac{(p-1)(m-1)}{2}} \sum_{\begin{matrix} \beta+\gamma+1=p \\ \beta,\gamma \geq 0 \end{matrix}} (-1)^\beta \dfrac{q^{\beta m+\frac{\gamma(\gamma+1)}{2}}}{[\beta]![\gamma]!(1-q^p)}\prod_{i=-\gamma}^\beta (q^i-\lambda q) $$


Chern-Simons Theory approach

For a general torus link $K(p,m)$, it can be viewed as a $d$-component link, where $d=\text{gcd}(p,m)$, with each component being a $(P,M)$-torus knot, where $\dfrac{P}{M}$ is the reduced form of the fraction $\dfrac{p}{m}$. We can then split the manifold $S^3$ into pieces with toroidal boundaries such that each piece contains one $K(P,M)$, schematically shown below: Splitting of the torus link Then by the spirit of the partition function, we have $$V_{\text{Cl}((\sigma_1 \sigma_2 \cdots \sigma_{p-1})^m)}(q, \lambda) = \left(V_{\text{Cl}((\sigma_1 \sigma_2 \cdots \sigma_{P-1})^M)}(q, \lambda) \right)^d =\left( \left(\dfrac{1-q}{1-\lambda q} \right) \lambda^{\frac{(p-d)(m-d)}{2d^2}} \sum_{\begin{matrix} \beta+\gamma+1=\frac pd \\ \beta,\gamma \geq 0 \end{matrix}} (-1)^\beta \dfrac{q^{\beta m+\frac{\gamma(\gamma+1)}{2}}}{[\beta]![\gamma]!(1-q^\frac pd)}\prod_{i=-\gamma}^\beta (q^i-\lambda q) \right)^d = \left(\dfrac{1-q}{1-\lambda q} \right)^d \lambda^{\frac{(p-d)(m-d)}{2d}} \left(\sum_{\begin{matrix} \beta+\gamma+1=\frac pd \\ \beta,\gamma \geq 0 \end{matrix}} (-1)^\beta \dfrac{q^{\beta m+\frac{\gamma(\gamma+1)}{2}}}{[\beta]![\gamma]!(1-q^\frac pd)}\prod_{i=-\gamma}^\beta (q^i-\lambda q) \right)^d$$

Similarly, for the tst links, we have the following splitting of $S^3$ into $(d+1)$ pieces: Splitting of the tst link where the rightmost knot is the unknot $O$.

Thus we have $$V_{\text{Cl}((\sigma_1^2 \sigma_2 \cdots \sigma_p)^m)}(q, \lambda) = \left(V_{\text{Cl}((\sigma_1 \sigma_2 \cdots \sigma_{P-1})^M)}(q, \lambda) \right)^d V_{O}(q, \lambda) = \left(V_{\text{Cl}((\sigma_1 \sigma_2 \cdots \sigma_{P-1})^M)}(q, \lambda) \right)^d = \left(\dfrac{1-q}{1-\lambda q} \right)^d \lambda^{\frac{(p-d)(m-d)}{2d}} \left(\sum_{\begin{matrix} \beta+\gamma+1=\frac pd \\ \beta,\gamma \geq 0 \end{matrix}} (-1)^\beta \dfrac{q^{\beta m+\frac{\gamma(\gamma+1)}{2}}}{[\beta]![\gamma]!(1-q^\frac pd)}\prod_{i=-\gamma}^\beta (q^i-\lambda q) \right)^d$$


Ocneanu trace approach

First consider the torus links. I will start with the easiest case $\sigma_1 \sigma_2 \cdots \sigma_p$. The Ocneanu trace is obviously $z^n$.

Then I will try $(\sigma_1 \sigma_2 \cdots \sigma_p)^2$. Denote $\beta \sim_O \beta'$ if they have the same Ocneanu traces, i.e. $\text{tr}(\beta) = \text{tr}(\beta')$, and $\beta \sim_M \beta'$ if they are related by a sequence of Markov moves. We have $$(\sigma_1 \sigma_2 \cdots \sigma_p)^2 $$ $$= \sigma_1 \sigma_2 \cdots \sigma_p\sigma_1 \sigma_2 \cdots \sigma_p $$ $$= \sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_p \sigma_{p-1} \sigma_p $$ $$\sim_M \sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-1} \sigma_p \sigma_{p-1} $$ $$\sim_O z \sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-1}^2 $$ $$\sim_O z(q-1) \sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-1} + zq \sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-2}$$ $$\sim_O z(q-1) (\sigma_1 \sigma_2 \cdots \sigma_{p-1})^2 + z^2q \sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-2}$$ $$\sim_O z(q-1) (\sigma_1 \sigma_2 \cdots \sigma_{p-1})^2 + z^2q (\sigma_1 \sigma_2 \cdots \sigma_{p-2})^2$$ Writing $tr((\sigma_1 \sigma_2 \cdots \sigma_p)^2) = T(2,p)$, we have the recurrence relation $$T(2,p) = z(q-1) T(2,p-1) + z^2qT(2,p-2)$$ which is second-order, homogeneous and has constant coefficients (no dependance on $p$). The characteristic equation is given by $$\lambda^2 - z(q-1) \lambda - z^2q = 0$$ Solving the quadratic equation gives $$\lambda = \dfrac{z(q-1) \pm \sqrt{(z(q-1))^2 - 4(-z^2q)}}{2} = \dfrac{z(q-1) \pm \sqrt{z^2q^2 - 2z^2q + z^2 + 4z^2q}}{2} = \dfrac{z(q-1) \pm \sqrt{z^2(q + 1)^2}}{2} = \dfrac{z(q-1) \pm z(q+1)}{2}$$ We have $\lambda = zq$ or $-z$. Hence $$T(2,p) = a(zq)^p + b(-z)^p$$ for some $a$ and $b$.

The initial values are given by $$T(2,1) = \text{tr}(\sigma_1^2) = (q-1)\text{tr}(\sigma_1) + q = (q-1)z + q$$ and $$T(2,2) = \text{tr}(\sigma_1\sigma_2\sigma_1\sigma_2) = \text{tr}(\sigma_1^2\sigma_2\sigma_1) = z\text{tr}(\sigma_1^3) = z(q-1)\text{tr}(\sigma_1^2) + zq \text{tr}(\sigma_1) = z(q-1)((q-1)z + q) + z^2q = z^2(q-1)^2 +zq(q-1) + z^2q$$ Substitution gives $$azq - bz = (q-1)z + q$$ $$a(zq)^2 + bz^2 = z^2(q-1)^2 +zq(q-1) + z^2q$$ Cramer's rule gives $$a = \dfrac{\begin{vmatrix} (q-1)z + q & -z \\ z^2(q-1)^2 +zq(q-1) + z^2q & z^2 \end{vmatrix}} {\begin{vmatrix} zq & -z \\ (zq)^2 + zq & z^2 \end{vmatrix}} =\dfrac{z\begin{vmatrix} (q-1)z + q & -1 \\ z^2(q-1)^2 +zq(q-1) + z^2q & z \end{vmatrix}} {z^2q\begin{vmatrix} 1 & -1 \\ zq + 1 & z \end{vmatrix}} =\dfrac{(q-1)z^2 + qz + z^2(q-1)^2 +zq(q-1) + z^2q}{zq(z+zq+1)} =\dfrac{zq + z^2q(q-1) +zq(q-1) + z^2q}{zq(z+zq+1)} =\dfrac{q(z + 1)}{z+zq+1} $$ and $$b = \dfrac{\begin{vmatrix} zq & (q-1)z + q \\ (zq)^2 & z^2(2q-1) + zq \end{vmatrix}} {\begin{vmatrix} zq & -z \\ (zq)^2 + zq & z^2 \end{vmatrix}} =\dfrac{zq\begin{vmatrix} 1 & (q-1)z + q \\ zq & z^2(q-1)^2 +zq(q-1) + z^2q \end{vmatrix}}{z^2q(z+zq+1)} =\dfrac{zq (z^2(q-1)^2 +zq(q-1) + z^2q - ((q-1)z^2q + zq^2))}{z^2q(z+zq+1)} =\dfrac{z(z-q)}{z(z+zq+1)} =\dfrac{z - q}{z+zq+1} $$ Hence $$\text{tr}((\sigma_1 \sigma_2 \cdots \sigma_p)^2) = \dfrac{q(z + 1)(zq)^p}{z+zq+1} + \dfrac{(z - q)(-z)^p}{z+zq+1} = \dfrac{q(z + 1)(zq)^p + (z - q)(-z)^p}{z+zq+1}$$

Now we try $(\sigma_1 \sigma_2 \cdots \sigma_p)^3$. By the same token, we have $$\sigma_1 \sigma_2 \cdots \sigma_p\sigma_1 \sigma_2 \cdots \sigma_p\sigma_1 \sigma_2 \cdots \sigma_p$$ $$=\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_p\sigma_{p-1}\sigma_p\sigma_1 \sigma_2 \cdots \sigma_p$$ $$\sim_M \sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_p\sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_p$$ $$\sim_M \sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-1}^2\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_p\sigma_{p-1}$$ $$\sim_O z\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-1}^2\sigma_1 \sigma_2 \cdots \sigma_{p-1}^2$$ $$\sim_O z(q-1)(\sigma_1 \sigma_2 \cdots \sigma_{p-1})^3 + zq\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-1}^2$$ $$\sim_O z(q-1)(\sigma_1 \sigma_2 \cdots \sigma_{p-1})^3 + zq(q-1)\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-1} + zq^2\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-2}$$ $$\sim_O z(q-1)(\sigma_1 \sigma_2 \cdots \sigma_{p-1})^3 + zq(q-1)\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-1} + z^2q^2(\sigma_1 \sigma_2 \cdots \sigma_{p-2})^3$$

But $$\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-1} $$ $$=\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_{p-3}\sigma_{p-2} \sigma_{p-1}$$ $$\sim_M \sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_{p-2}\sigma_{p-3} \sigma_{p-1}$$ $$= \sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_{p-1}\sigma_{p-2}\sigma_{p-1}\sigma_{p-3}$$ $$\sim_M \sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_{p-2}\sigma_{p-1}\sigma_{p-2}\sigma_{p-3}$$ $$\sim_O z\sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_{p-2}^2\sigma_{p-3}$$ $$\sim_O z ((q-1) \sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_{p-2}\sigma_{p-3} + q\sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_1 \sigma_2 \cdots \sigma_{p-3}^2)$$ $$\sim_O z ((q-1) \sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_{p-3}\sigma_{p-2} + qz(\sigma_1 \sigma_2 \cdots \sigma_{p-3})^2\sigma_1 \sigma_2 \cdots \sigma_{p-3}^2)$$ $$\sim_O z ((q-1) \sigma_1 \sigma_2 \cdots \sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_{p-2}\sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_{p-2} + qz(\sigma_1 \sigma_2 \cdots \sigma_{p-3})^2\sigma_1 \sigma_2 \cdots \sigma_{p-3}^2)$$ $$= z ((q-1) (\sigma_1 \sigma_2 \cdots \sigma_{p-2})^3 + qz(\sigma_1 \sigma_2 \cdots \sigma_{p-3})^2\sigma_1 \sigma_2 \cdots \sigma_{p-3}^2)$$ $$\sim_O z(q-1) (\sigma_1 \sigma_2 \cdots \sigma_{p-2})^3 + q(q-1)z^2(\sigma_1 \sigma_2 \cdots \sigma_{p-3})^3 +q^2z^2(\sigma_1 \sigma_2 \cdots \sigma_{p-3})^2\sigma_1 \sigma_2 \cdots \sigma_{p-4}$$ $$\sim_M z(q-1) (\sigma_1 \sigma_2 \cdots \sigma_{p-2})^3 + q(q-1)z^2(\sigma_1 \sigma_2 \cdots \sigma_{p-3})^3 +q^2z^2 \sigma_1 \sigma_2 \cdots \sigma_{p-3}\sigma_1 \sigma_2 \cdots \sigma_{p-4} \sigma_1 \sigma_2 \cdots \sigma_{p-3}$$ Writing $\text{tr}((\sigma_1 \sigma_2 \cdots \sigma_p)^3) = T(3, p)$ and $\text{tr}(\sigma_1 \sigma_2 \cdots \sigma_p\sigma_1 \sigma_2 \cdots \sigma_{p-1}\sigma_1 \sigma_2 \cdots \sigma_p) = U(3, p)$, we have $$U(3, p-1) = z(q-1)T(3,p-2)+q(q-1)z^2T(3,p-3)+q^2z^2U(3,p-3)$$ and $$T(3,p) = z(q-1)T(3,p-1) + zq(q-1)U(3,p-1) + z^2q^2T(3,p-2)$$ Rearrange the last relation to give $$U(3,p-1) = \dfrac{T(3,p)-z(q-1)T(3,p-1)-z^2q^2T(3,p-2)}{zq(q-1)} =\dfrac{T(3,p)}{zq(q-1)}-\dfrac{T(3,p-1)}{q}-\dfrac{zqT(3,p-2)}{q-1}$$ Substitute into the first relation to give $$\dfrac{T(3,p)}{zq(q-1)}-\dfrac{T(3,p-1)}{q}-\dfrac{zqT(3,p-2)}{q-1}= z(q-1)T(3,p-2)+q(q-1)z^2T(3,p-3)+q^2z^2\left(\dfrac{T(3,p-2)}{zq(q-1)}-\dfrac{T(3,p-3)}{q}-\dfrac{zqT(3,p-4)}{q-1}\right)$$

This recurrence relation needs to be solved subject to $$U(3, 2) = \text{tr}(\sigma_2\sigma_1\sigma_2) = \text{tr}(\sigma_1\sigma_2\sigma_1) = z\text{tr}(\sigma_1^2) = z(q-1)\text{tr}(\sigma_1)+zq = z^2(q-1)+zq$$ $$T(3, 1) = \text{tr}(\sigma_1^3) = (q-1)\text{tr}(\sigma_1^2)+q\text{tr}(\sigma_1) = (q-1)^2\text{tr}(\sigma_1)+ (q-1)q + qz = (q-1)^2z + (q-1)q + qz$$ $$T(3, 2) = \text{tr}((\sigma_1\sigma_2)^3) = \text{tr}(\sigma_1\sigma_2\sigma_1\sigma_2\sigma_1\sigma_2) = \text{tr}(\sigma_2\sigma_1\sigma_2^2\sigma_1\sigma_2) = (q-1)\text{tr}(\sigma_2\sigma_1\sigma_2\sigma_1\sigma_2) + q\text{tr}(\sigma_2\sigma_1\sigma_1^2\sigma_2) = (q-1)\text{tr}(\sigma_2\sigma_1\sigma_1\sigma_2\sigma_1) + q(q-1)\text{tr}(\sigma_2\sigma_1\sigma_1\sigma_2) + q^2\text{tr}(\sigma_2\sigma_1\sigma_2) = (q-1)^2\text{tr}(\sigma_2\sigma_1\sigma_1\sigma_2\sigma_1) + (q-1)q\text{tr}(\sigma_2\sigma_2\sigma_1) + q(q-1)\text{tr}(\sigma_2^2\sigma_1\sigma_1) + q^2\text{tr}(\sigma_1\sigma_2\sigma_1) = (q-1)^2\text{tr}(\sigma_1\sigma_1\sigma_2\sigma_1\sigma_2) + (q-1)q\text{tr}(\sigma_2\sigma_2\sigma_1) + q(q-1)((q-1)\text{tr}(\sigma_2\sigma_1^2)+q\text{tr}(\sigma_1\sigma_1))+ q^2z\text{tr}(\sigma_1^2) = (q-1)^2\text{tr}(\sigma_1\sigma_1\sigma_1\sigma_2\sigma_1) + (q-1)q\text{tr}(\sigma_1\sigma_2\sigma_1) + q(q-1)((q-1)z\text{tr}(\sigma_1^2)+qtr(\sigma_1^2))+ q^2z\text{tr}(\sigma_1^2) = (q-1)^2z\text{tr}(\sigma_1^4) + (q-1)qz\text{tr}(\sigma_1^2) + q(q-1)((q-1)z\text{tr}(\sigma_1^2)+qtr(\sigma_1^2))+ q^2z\text{tr}(\sigma_1^2) = (q-1)^2z\text{tr}(\sigma_1^4) + ((q-1)qz + q(q-1)((q-1)z+q)+ q^2z)\text{tr}(\sigma_1^2)$$ But $$\sigma_1^2 \sim_O (q-1)\sigma_1 + q \sim_O (q-1)z + q = qz-z+q$$ and $$\sigma_1^4 \sim_O (q-1)\sigma_1^3 + q\sigma_1^2 \sim_O (q-1)((q-1)\sigma_1^2 + q\sigma_1) + q((q-1)z + q) \sim_O (q-1)((q-1)((q-1)z + q) + qz) + q((q-1)z + q)$$ $$=q^3 z - q^2 z + q z - z + q^3 - q^2 + q$$ Hence $$T(3, 2) = (q-1)^2z(q-1)((q-1)((q-1)z + q) + qz) + q((q-1)z + q) + ((q-1)qz + q(q-1)((q-1)z+q)+ q^2z)((q-1)z + q)$$ $$=q^5 z^2 + q^5 z - 3 q^4 z^2 - 2 q^4 z + q^4 + 6 q^3 z^2 + 4 q^3 z - q^3 - 7 q^2 z^2 - 2 q^2 z + q^2 + 4 q z^2 - z^2$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.